PIVET rFSH dosing algorithms for individualized controlled ovarian stimulation enables optimized pregnancy productivity rates and avoidance of ovarian hyperstimulation syndrome - Yovich, John; Alsbjerg, B.; Conceicao, J.; Hinchliffe, P.; Keane, Kevin (Dove Medical Press Ltd., 2016)
© 2016 Yovich et al.The first PIVET algorithm for individualized recombinant follicle stimulating hormone (rFSH) dosing in in vitro fertilization, reported in 2012, was based on age and antral follicle count grading with adjustments for anti-Müllerian hormone level, body mass index, day-2 FSH, and smoking history. In 2007, it was enabled by the introduction of a metered rFSH pen allowing small dosage increments of ~8.3 IU per click. In 2011, a second rFSH pen was introduced allowing more precise dosages of 12.5 IU per click, and both pens with their individual algorithms have been applied continuously at our clinic. The objective of this observational study was to validate the PIVET algorithms pertaining to the two rFSH pens with the aim of collecting =15 oocytes and minimizing the risk of ovarian hyperstimulation syndrome. The data set included 2, 822 in vitro fertilization stimulations over a 6-year period until April 2014 applying either of the two individualized dosing algorithms and corresponding pens. The main outcome measures were mean oocytes retrieved and resultant embryos designated for transfer or cryopreservation permitted calculation of oocyte and embryo utilization rates. Ensuing pregnancies were tracked until live births, and live birth productivity rates embracing fresh and frozen transfers were calculated. Overall, the results showed that mean oocyte numbers were 10.0 for all women <40 years with 24% requiring rFSH dosages <150 IU. Applying both specific algorithms in our clinic meant that the starting dose was not altered for 79.1% of patients and for 30.1% of those receiving the very lowest rFSH dosages (=75 IU). Only 0.3% patients were diagnosed with severe ovarian hyperstimulation syndrome, all deemed avoidable due to definable breaches from the protocols. The live birth productivity rates exceeded 50% for women <35 years and was 33.2% for the group aged 35–39 years. Routine use of both algorithms led to only 11.6% of women generating.15 oocytes, significantly lower than recently published data applying conventional dosages (38.2%; P<0.0001). When comparing both specific algorithms to each other, the outcomes were mainly comparable for pregnancy, live birth, and miscarriage rate. However, there were significant differences in relation to number of oocytes retrieved, but the mean for both the algorithms remained well below 15 oocytes. Consequently, application of both these algorithms in our in vitro fertilization clinic allows the use of both the rFSH products, with very similar results, and they can be considered validated on the basis of effectiveness and safety, clearly avoiding ovarian hyperstimulation syndrome.